Direct pre- and post-ablation cardiac magnetic resonance imaging of tissue characteristics in patients with typical atrial flutter. (19th May 2022) - Nies, HMJM; Bijvoet, GP; Chaldoupi, SM; Vernooy, K; Linz, D; Wildberger, JE; Holtackers, RJ; Mihl, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Real-time cardiac magnetic resonance (CMR) imaging as guidance in electrophysiology (EP) procedures enables a detailed overview of the anatomy of the heart and surrounding structures, active and passive catheter tracking, and real-time visualisation of ablation lesions throughout the ablation procedure, without using fluoroscopy. Purpose: To evaluate ablation induced changes in tissue characteristics of the cavotricuspid isthmus (CTI), directly following typical atrial flutter ablation in an interventional cardiac magnetic resonance (iCMR) suite. Methods: Nine patients with symptomatic typical atrial flutter were referred for CTI ablation in an iCMR suite. Procedures were performed using a 1.5T MRI scanner. Pre-ablation imaging included T2-weighted edema imaging in the right anterior oblique (RAO) and transversal view. During the ablation procedure, CMR imaging facilitated active tracking and real-time navigation of both diagnostic and ablation catheters, as well as visualisation of the ablated tissue. Post-ablation imaging to evaluate the target tissue again included T2-weighted edema imaging as well as dark-blood late gadolinium enhancement (LGE) imaging. Data regarding post-ablation imaging findings, ablation outcome, and complications were collected for all patients. All patients provided written informed consent. Results: In eight of the nine patients, T2-weighted imaging was successfully performed pre- and post-ablation, which identified myocardial edema at the CTI ablation line in all patients (Figure 1A-B). Due to time restraints, post-ablation LGE imaging was performed in five patients, which showed pathological signal intensity at the level of the CTI in all five patients (Figure 1C). Bidirectional block of the CTI was confirmed by differential pacing in eight patients. No complications occurred during or immediately after the procedures. In one patient, the registration of intracardiac electrograms was not possible due to technical problems and the patient was transferred to a conventional EP lab to complete the ablation following our predefined bailout procedure. Conclusion: Real-time CMR guided CTI ablation in patients with typical atrial flutter is safe and successful. CMR enables accurate visualisation of the CTI line and provides immediate post-ablation evaluation of tissue characteristics at the ablation target location. Figure 1. T2-weighted edema cardiac magnetic resonance (CMR) imaging in the right anterior oblique (RAO) view acquired pre- (A) and post-ablation (B) during interventional CMR ablation therapy. Late gadolinium enhancement (LGE) CMR in the RAO view post-ablation (C) of the same patient. The blue arrowheads indicate the cavotricuspid isthmus (CTI) line. High signal intensity at the level of CTI is observed post-ablation on both T2-weighted (indicating edema) and LGE (indicating cell membrane rupture) images.